APLIKASI PROSES BIOLOGI ANAEROBIK PADA PENGOLAHAN AIR LIMBAH ORGANIK BERKONSENTRASI GARAM TINGGI Ã¢â‚¬Å“STUDI KASUS INDUSTRI UME BOSHIÃ¢â‚¬Â - Mahmud, Ikbal (Center for Environmental Technology, 2005)
Anaerobic treatment of wastewater with high organic and salt content but low pH (TOC, 14 g/l; salt, 150 g/l; pH,2.7) generated during an Ã¢â‚¬Å“ume boshiÃ¢â‚¬Â manufacturing process was investigated. Five-fold-diluted Ã¢â‚¬Å“ume boshiÃ¢â‚¬Â effluent was treated by a draw-and-fill method at a volumetric TOC (total organic carbon) loading rate of 3.0 Ã‚Â g/l/d with a TOC removal efficiency of 75%. Five-fold-diluted Ã¢â‚¬Å“ome boshiÃ¢â‚¬Â effluent was also treated in an anaerobic fluidized-bed reactor (AFBR) at a maximum volumetric TOC loading rate of 3.0 g/l/d, which gave almost the same results as the draw-and-fill method. However, ten-fold-diluted Ã¢â‚¬Å“ome boshiÃ¢â‚¬Â effluent could be treated in the AFBR at a maximum volumetric TOC loading rate of 11 g/l/d with a TOC removal efficiency of 85%. The methane content in the evolved gas was high, being 70%. The red pigment in the Ã¢â‚¬Å“ome boshiÃ¢â‚¬Â effluent was completely decolorized by the anaerobic treatment. Ã‚Â Key words :, Anaerobic fluidized-bed reactor, Ã¢â‚¬Å“Ume boshiÃ¢â‚¬ÂCo2+ and Ni2+ ions, decolorization